Coated separator, manufacturing method for coated separator, and battery

A structured coating layer design with uniform nanofiber and ceramic particle distribution in coated separators addresses the peeling and conductivity issues, enhancing heat resistance and lithium ion conductivity while maintaining battery capacity.

JP2024546399AActive Publication Date: 2024-12-23SHENZHEN SENIOR TECH MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024541210
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2022-09-26
Publication Date
2024-12-23
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The bond between the ceramic layer and the separator in coated separators is weak, leading to peeling, reduced heat resistance, and decreased lithium ion conductivity due to non-uniform pore sizes and irregular nanofiber distribution.

Method used

A coated separator with a structured coating layer design, comprising a first coating layer of large-sized nanofibers and ceramic particles, and a second coating layer of small-sized nanofibers and ceramic particles, ensuring uniform pore sizes and improved adhesion, enhancing heat resistance and lithium ion conductivity.

Benefits of technology

The structured coating layer design improves heat resistance, lithium ion conductivity, and electrochemical stability, reducing the risk of lithium dendrite formation and maintaining high battery capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546399000001_ABST
    Figure 2024546399000001_ABST
Patent Text Reader

Abstract

A coated separator, a manufacturing method for a coated separator, and a battery in which first nanofibers (21) of similar size are mixed in a first coating layer (20) and second nanofibers (31) of similar size are mixed in a second coating layer (30), thereby avoiding the problem that nanofibers of similar surface energy tend to aggregate due to the large difference in surface energy caused by the large difference in size between different nanofibers, and greatly improving the uniformity of mixing between the nanofibers. Furthermore, by making the first coating layer (20) a mixture of large-sized first nanofibers (21) and large-particle-diameter first ceramic particles (22), and by making the second coating layer (30) a mixture of small-sized second nanofibers (31) and small-particle-diameter second ceramic particles (32), the first coating layer (20) has a large pore size and a strong skeletal structure, and the coated separator can be maintained to maintain high heat resistance and high permeability. The second coating layer with a small pore size can improve the conductivity of lithium ions, and the risk of electrochemical stability due to high-temperature exposure or long-term cycles is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of battery separator technology, and more particularly to coated separators, methods for making coated separators, and batteries. [Background technology]

[0002] The separator is one of the main components of lithium batteries, and its performance has a very important impact on the overall performance of lithium batteries, and is one of the key technologies that restrict the development of lithium batteries. As the application fields of lithium batteries continue to expand and the impact of lithium battery products on people's lives continues to become more and more profound, people's requirements for lithium battery performance are also increasing. In order to meet the development requirements of lithium batteries, the separator, as an important component of lithium batteries, not only should have good chemical stability and low manufacturing costs, but also further improve the safety performance of lithium-ion batteries, which is an important trend in the current development of lithium batteries.

[0003] In the related art, the coating separator may include a base film and a coating layer coated on at least one surface of the base film, and a ceramic layer may be coated on the surface of the coating separator to improve the heat resistance of the separator. However, the two-phase interface between the ceramic layer and the separator is weakly bonded and is prone to separation at high temperatures, which causes the ceramic layer to peel off and the separator substrate to melt, resulting in a decrease in heat resistance. Meanwhile, the ceramic layer on the surface increases the conduction distance of lithium ions, further reducing the conductivity of lithium ions, and the large pores make it difficult to maintain the liquid electrolyte well. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a coated separator, a method for producing the coated separator, and a battery in order to improve the performance of the separator. [Means for solving the problem]

[0005] According to a first aspect of the present invention, a coating separator is provided, the coating separator comprising a base membrane and a coating layer structure disposed on at least one surface of the base membrane, the coating layer structure comprising at least a first coating layer and a second coating layer, wherein the first coating layer is a coating layer of the base membrane. At least one a second coating layer disposed on a surface of the base membrane, the second coating layer disposed on a side of the first coating layer away from the base membrane, the first coating layer comprising a first nanofiber material and first ceramic particles, and the second coating layer comprising a second nanofiber material and second ceramic particles; the first nanofiber material comprises a number of first nanofibers and the second nanofiber material comprises a number of second nanofibers; The difference in length between some of the first nanofibers is 500 nm or less, the difference in length between some of the second nanofibers is 200 nm or less, the length of the first nanofibers is greater than the length of the second nanofibers, and the average particle diameter of the first ceramic particles is greater than the average particle diameter of the second ceramic particles.

[0006] Optionally, the first nanofibers have a length of 500 to 1000 nm, and the first ceramic particles have an average particle size of 100 to 600 nm.

[0007] Optionally, the mass ratio of the first nanofiber material to the first ceramic particles is 5:1 to 1:5.

[0008] Optionally, the second nanofibers have a length of 100 to 300 nm, and the second ceramic particles have an average particle size of 10 to 60 nm.

[0009] Optionally, the mass ratio of the second nanofiber material to the second ceramic particles is 5:1 to 1:5.

[0010] Optionally, the first nanofibers have a diameter of 5-50 nm, and the second nanofibers have a diameter of 5-50 nm.

[0011] Optionally, the ratio of the thickness of the first coating layer to the thickness of the second coating layer is greater than two.

[0012] Optionally, at least one additional coating layer is further included between the first coating layer and the second coating layer.

[0013] Optionally, fast lithium ion conductive functional groups are grafted onto the surface of the second ceramic particles; Furthermore, the high-speed lithium ion conductive functional group includes any one of hydroxyl (-OH), carbonyl (-C=O), fluorine (-F) and carboxyl (-COOH).

[0014] Optionally, the first ceramic particles and Before The second ceramic particle At least one of is an inorganic compound that has a melting point of 200°C or higher, is electrically insulating, and is electrochemically stable within the range of use of lithium batteries.

[0015] Optionally, the coating separator comprises at least: a) ionic conductivity ≧1.2 mS / cm; b) Capacity maintenance rate ≧98%, c) Thermal shrinkage at 180℃ / h ≦5%; Satisfy one of the following conditions.

[0016] According to a second aspect of the present invention, there is provided a method for producing a coated separator according to the first aspect and its optional solutions, the method including producing a paste and forming a film by coating, In preparing the paste, a first paste including first ceramic particles and a first nanofiber material is prepared, and a second paste including second ceramic particles and a second nanofiber material is prepared; In the film formation by coating, the first paste is coated on at least one surface of the base film to form a first coating layer, and the second paste is coated on the side of the first coating layer away from the base film to form a second coating layer; moreover, preparing the first paste includes dispersing first ceramic particles in a first solvent to obtain a first ceramic dispersion, dispersing a first nanofiber material in a second solvent to obtain a first nanofiber dispersion, and mixing the first ceramic dispersion and the first nanofiber dispersion to obtain the first paste; Producing the second paste includes dispersing the second ceramic particles in a third solvent to obtain a second ceramic dispersion, dispersing the second nanofiber material in a fourth solvent to obtain a second nanofiber dispersion, and mixing the second ceramic dispersion and the second nanofiber dispersion to obtain the second paste.

[0017] Optionally, prior to the preparation of the paste, the method further comprises screening of ceramics; In the selection of the ceramics, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the first ceramic particles have an average particle size of 100 to 600 nm, and the second ceramic particles have an average particle size of 10 to 60 nm; The method further includes a pretreatment of the ceramic, in which the second ceramic particles are subjected to a grafting reaction with a grafting object to graft high-speed lithium ion conductive functional groups onto the surfaces of the second ceramic particles.

[0018] Optionally, the grafting object includes any one of polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, and methyl isopropyl ketone.

[0019] According to a third aspect of the present invention, there is provided a battery, the battery comprising a coated separator according to the first aspect and its alternative solutions, or a coated separator produced by the method for producing a coated separator according to the second aspect and its alternative solutions, Furthermore, the battery is a lithium battery.

[0020] In the coated separator, the manufacturing method for the coated separator, and the battery provided by the present invention, first nanofibers having similar sizes are mixed in the first coating layer, and second nanofibers having similar sizes are mixed in the second coating layer, thereby avoiding the problem that nanofibers having similar surface energies tend to aggregate due to the large difference in surface energy caused by the large difference in size between different nanofibers, and greatly improving the mixing uniformity between the nanofibers. In addition, the first coating layer is made by mixing large-sized first nanofibers and large-sized first ceramic particles to form a first mixed material layer with a large pore size and a uniform pore size, which is disposed on the surface of the base membrane and has a large pore size and a strong skeleton structure, so that the coated separator can maintain high heat resistance and high permeability. The second coating layer is made by mixing small-sized second nanofibers and small-sized second ceramic particles to form a second mixed material layer with a small pore size and a uniform pore size. ,hair Due to tubule action The small pore size of the coating separator It has a strong adsorption ability for the electrolyte, which can improve the conductivity of lithium ions, thereby reducing the possibility of lithium dendrites occurring and reducing the risk of electrochemical stability due to exposure to high temperatures or long-term cycles. [Brief description of the drawings]

[0021] In order to more clearly describe the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces drawings that need to be used in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without making any creative efforts. [Figure 1] FIG. 2 is a schematic diagram of the local structure of a coating separator in one embodiment of the present invention. [Diagram 2] 4 is a flowchart of a method for manufacturing a coating separator in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the technical solutions in the embodiments of the present invention will be described clearly and completely with reference to the drawings related to the embodiments of the present invention, and obviously, the described embodiments are only some embodiments of the present invention, and not all of the embodiments thereof. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without any creative efforts shall fall within the protection scope of the present invention.

[0023] In describing the present specification, it should be understood that the orientations or positional relationships indicated by terms such as "upper", "lower", "top", "bottom", "lower surface", "top" and the like are based on the orientations or positional relationships shown in the drawings, and are merely for ease of and simplification of the present invention, and are not to be understood as limiting the present invention, since they do not indicate or suggest that the devices or elements shown have a particular orientation and must be constructed and operated in a particular orientation.

[0024] In describing the present specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying a relative importance or a number of the technical features indicated, whereby a feature qualified by "first" or "second" may explicitly or implicitly include one or more of said features.

[0025] In the description of the present invention, "plurality" means a plurality, for example two, three, four, etc., unless otherwise clearly and specifically limited.

[0026] In the description of the present invention, the term "connection" should be understood in a broad sense unless otherwise clearly specified and limited, and may be, for example, a fixed connection, a removable connection, or an integrated one, a mechanical connection, an electrical connection or a mutually communicable one, a direct connection, an indirect connection via an intermediate medium, an internal communication between two elements, or an interaction between two elements. A person skilled in the art can understand the specific meaning of the above terms in the present invention according to the specific situation.

[0027] The technical solutions of the present invention are described in detail below using specific embodiments. Some of the following specific embodiments can be combined with each other, and the same or similar concepts or processes may be omitted in some embodiments.

[0028] Before proposing the present application, the applicant conducted a series of studies and experiments on conventional separators, To solve the problem of the ceramic layer being easily peeled off, this field proposes that one-dimensional nanomaterials can be added to the coating layer.

[0029] In order to solve problems such as the messy and irregular deposition method of the one-dimensional nano material in the coating layer, too many gaps, and few contact points, the applicant proposes a corresponding solution, which is to reduce the length of the one-dimensional nano material layer by layer according to the coating layer (embodied in the reduction of the described value of the length of the one-dimensional nano material in each material layer), so that the pores are large when the long nano material is deposited, and the lower the layer, the larger the gaps are, and the shorter nano material in the upper layer can fill these gaps to a certain extent. When deposited layer by layer, there are not too many gaps inside the coating layer, and there are more contact points, so that when heat is applied, the tight structure of the coating layer can suppress the occurrence of thermal deformation of the separator, thereby improving the heat resistance of the coated separator. Regarding this solution, the applicant has also proposed a patent application (application number: PCT / CN2022 / 077087, filing date: 2022.02.21), and this application incorporates the entire contents of PCT / CN2022 / 077087 into this specification, i.e., the entire contents of PCT / CN2022 / 077087 may serve as support for this application.

[0030] In order to solve the problem that the deposition density of the one-dimensional nanofibers is too large due to the deposition method of the one-dimensional nanofibers decreasing layer by layer, which blocks the lithium ion conduction channel, affects the lithium ion conductivity, and limits the performance of the separator, the applicant proposes a corresponding solution, which can effectively increase the ion conduction rate by introducing ceramic particles into the one-dimensional nanomaterial coating layer. Regarding this solution, the applicant also proposes a patent application (application number: PCT / CN2022 / 108551, filing date: 2022.07.28), which incorporates the entire contents of PCT / CN2022 / 108551 into this specification, i.e., the entire contents of PCT / CN2022 / 108551 can be used as support for this application.

[0031] However, in further research, the applicant found that although the above solution can avoid the stacking density of one-dimensional nanomaterials being too large by using ceramic particles, and can form an effective lithium ion conducting channel, improving the conductivity of lithium ions, the performance of the separator as a whole is still not ideal enough. Through research and testing, the applicant found that when the size difference between different nanofibers is too large, the difference in surface energy is large, so that nanofibers with similar surface energy are likely to aggregate, that is, the surface energy of small-sized nanofibers is large, and they are likely to aggregate with each other to form aggregates, and are mixed in contact with large-sized nanofibers. In this way, the small-sized nanofibers cannot fully perform their expected performance, and the ceramic particles are not divided according to different sizes of nanofibers, so the performance of the separator is limited.

[0032] Based on this discovery, the applicant has obtained the technical solution of the present application through a series of research, testing and verification. Since the ordered arrangement of one-dimensional nanofibers is one of the applicant's major technical innovations, the further researched problems and the obtained solutions based on the ordered arrangement are also major technical innovations, and the entire research process should be an integral part of the solution and should be considered as a whole when evaluating the inventive step of the present application.

[0033] Referring to FIG. 1, an embodiment of the present invention provides a coating separator, the coating separator includes a base membrane 10 and a coating layer structure disposed on the base membrane 10, the coating layer structure includes a first coating layer 20 and a second coating layer 30, the first coating layer 20 is disposed on the surface of the base membrane 10, the second coating layer 30 is disposed on the side of the first coating layer 20 away from the base membrane 10, the first coating layer 20 includes a first nanofiber material and a first ceramic particle 22, the second coating layer 30 is disposed on the surface of the first coating layer 20 away from the base membrane 10, the first coating layer 20 includes a first nanofiber material and a first ceramic particle 22, and ... The coating layer 30 comprises a second nanofiber material and second ceramic particles 32, the first nanofiber material comprises several first nanofibers 21, the second nanofiber material comprises several second nanofibers 31, the difference in length between each of the first nanofibers 21 is 500 nm or less, the difference in length between each of the second nanofibers 31 is 200 nm or less, the length of the first nanofibers 21 is greater than the length of the second nanofibers 31, and the average particle diameter of the first ceramic particles 22 is greater than the average particle diameter of the second ceramic particles 32.

[0034] In the embodiment of the present invention, the difference in size between different nanofibers is too large, and the difference in surface energy between them is large, so that nanofibers with similar surface energy tend to aggregate, i.e., the surface energy of small-sized nanofibers is large, and they tend to aggregate with each other to form aggregates, and then come into contact with and mix with large-sized nanofibers. In view of the fact that small-sized nanofibers cannot fully demonstrate their performance, the uniformity of the mixture is greatly improved by mixing nanofibers with similar sizes, The uniformity of distribution of nanofibers due to their aggregation (due to differences in length)The first coating layer is made by mixing a first nanofiber having a large size with a first ceramic particle having a large particle size, thereby forming a first mixed material layer having a large pore size and a uniform pore size, the first mixed material layer is placed on the surface of the base membrane, and the pore size is large and the skeleton structure is strong, so that the coated separator can maintain high heat resistance and high permeability, and the second coating layer is made by mixing a second nanofiber having a small size with a second ceramic particle having a small particle size, thereby forming a second mixed material layer having a small pore size and a uniform pore size, such a small pore size has a strong adsorption ability for the electrolyte due to its capillary action, thereby improving the conductivity of lithium ions, thereby reducing the possibility of lithium dendrite generation and reducing the risk of electrochemical stability due to high temperature exposure or long-term cycles, thereby effectively improving the performance of the separator.

[0035] In a preferred embodiment, the length of the first nanofibers 21 is 500 to 1000 nm, and may be, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc., and the average particle diameter of the first ceramic particles 22 is 100 to 600 nm, and may be, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, etc. The first coating layer containing the first nanofibers and the first ceramic particles is placed on the surface of the base membrane to form a large pore size and a strong skeleton structure, so that the coating separator can maintain high heat resistance and high permeability.

[0036] In a preferred embodiment, the mass ratio of the first nanofiber material to the first ceramic particles 22 is 5:1 to 1:5. By setting the mass ratio of the first nanofiber material to the first ceramic particles 22 within this range, the coating layer can be maintained with excellent heat resistance and lithium ion conductivity. As a specific example, the mass ratio of the first nanofiber material to the first ceramic particles 22 may be, for example, any one or any two of 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, and 1:5. Of course, the mass ratio of the first nanofiber material to the first ceramic particles 22 may be, for example, any one or any two of 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, and 1:5. Fiber The mass ratio of the material to the first ceramic particles may be other values, and the specific numerical values ​​do not limit the present invention, and any ratio between 5:1 and 1:5 is within the scope of protection of the present invention.

[0037] In a preferred embodiment, the length of the second nanofibers 31 is 100 to 300 nm, and may be, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc., and the average particle diameter of the second ceramic particles 32 is 10 to 60 nm, and may be, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, etc. The second coating layer is disposed on the side away from the base film with respect to the first coating layer, and is a mixture of the second nanofibers and the second ceramic particles. Such a small pore diameter has a strong adsorption ability for the electrolyte due to its capillary action, and improves the conductivity of lithium ions, thereby reducing the possibility of lithium dendrites being generated and reducing the risk of electrochemical stability due to high temperature exposure or long-term cycles.

[0038] In a preferred embodiment, the mass ratio of the second nanofiber material to the second ceramic particles 32 is 5:1 to 1:5. By setting the mass ratio of the second nanofiber material to the second ceramic particles 32 within this range, the coating layer has excellent battery capacity retention rate and lithium ion conductivity. 32The mass ratio of the second nanoparticles to the first nanoparticles may be, for example, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, or any one of the ranges between any two of the ranges. Fiber The mass ratio of the material to the second ceramic particles may be other values, and the specific numerical values ​​do not limit the present invention, and any ratio between 5:1 and 1:5 is within the scope of protection of the present invention.

[0039] In a preferred embodiment, the first nanofiber has a diameter of 5 to 50 nm, and the second nanofiber has a diameter of 5 to 50 nm.

[0040] In a preferred embodiment, the ratio of the thickness of the first coating layer 20 to the thickness of the second coating layer 30 is greater than 2, so that the heat resistance of the coating separator can be more effectively improved.

[0041] As a preferred embodiment, at least one additional coating layer is further included between the first coating layer 20 and the second coating layer 30. For example, one additional coating layer, such as a third coating layer, may be further included between the first coating layer 20 and the second coating layer 30, or two additional coating layers, such as a third coating layer and a fourth coating layer, may be further included. Of course, other numbers of additional coating layers may be included. Here, the additional coating layer may be selected to have the same material and size as the first coating layer or the second coating layer, or may be selected to have a different material and size. That is, a third coating layer is provided between the first coating layer and the second coating layer, the third coating layer includes third ceramic particles having an average particle size of 100-600 nm and third nanofibers having a length-to-diameter ratio of ≦200, and the third ceramic particles and the third nanofibers are different in material and size from the second coating layer, or a third coating layer is provided between the first coating layer and the second coating layer, the third coating layer includes third ceramic particles having an average particle size of 10-60 nm and third nanofibers having a length-to-diameter ratio of ≦60, and the third ceramic particles and the third nanofibers are different in material and size from the first coating layer. Note that the number of coating layers in the coating separator, the selection of different interlayer materials, and the setting of sizes can be adjusted according to actual requirements, and this cannot be understood as limiting the present invention.

[0042] In a preferred embodiment, a fast lithium ion conductive functional group is grafted onto the surface of the second ceramic particles 32, and the fast lithium ion conductive functional group contained in a large amount on the surface of the second ceramic particles can greatly improve the lithium ion conduction ability. Furthermore, the fast lithium ion conductive functional group includes any one of hydroxyl (-OH), carbonyl (-C=O), fluorine (-F), and carboxyl (-COOH).

[0043] In a preferred embodiment, the first ceramic particles 22 and / or the second ceramic particles 32 are inorganic compounds having a melting point of 200° C. or more, having electrical insulation properties, and being electrochemically stable within the range of use of a lithium battery. For example, ceramics such as oxide-based ceramics such as alumina, silica, titanium oxide, zirconia, magnesia, ceria, yttria, and zinc oxide, nitride-based ceramics such as silicon nitride, titanium nitride, and boron nitride, silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, basic alumina (aluminum hydroxide oxide), potassium titanate, talc, kaolinite, kaolin, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand may be used alone or in combination.

[0044] In a preferred embodiment, the coating separator comprises at least: a) ionic conductivity ≧1.2 mS / cm; b) Capacity maintenance rate ≧98% c) Thermal shrinkage at 180℃ / h ≦5%; Satisfy one of the following conditions.

[0045] Also, referring to FIG. 2, an embodiment of the present invention further provides a method for manufacturing a coated separator according to the first aspect and its optional solution, the method including: manufacturing a first paste, manufacturing a second paste, and forming a film by coating; S1, in the preparation of a first paste, a first paste including first ceramic particles and a first nanofiber material is prepared; S2, in the preparation of a second paste, a second paste including second ceramic particles and a second nanofiber material is prepared; S3. In forming a film by coating, the first paste is coated on at least one surface of the base film to form a first coating layer, and the second paste is coated on the side of the first coating layer away from the base film to form a second coating layer.

[0046] Specifically, preparing the first paste includes dispersing first ceramic particles in a first solvent to obtain a first ceramic dispersion, dispersing a first nanofiber material in a second solvent to obtain a first nanofiber dispersion, and mixing the first ceramic dispersion and the first nanofiber dispersion to obtain a first paste; Producing the second paste includes dispersing the second ceramic particles in a third solvent to obtain a second ceramic dispersion, dispersing the second nanofiber material in a fourth solvent to obtain a second nanofiber dispersion, and mixing the second ceramic dispersion and the second nanofiber dispersion to obtain the second paste.

[0047] Here, it goes without saying that the first solvent, the second solvent, the third solvent, and the fourth solvent may be the same type of solvent or may be different, and the present invention is not limited thereto.

[0048] Here, the present invention does not limit the order of producing the first paste and the second paste, and the second paste may be produced first, and then the first paste.

[0049] In one example, the first solvent and the third solvent The medium is , each Water, N-methylpyrrolidone, ethanol, acetone, etc. At least one of the following is selected: The first ceramic particles and the second ceramic particles are dispersed by high-speed stirring, high-pressure homogenization, sand mill dispersion, etc. each The first ceramic particles and the second ceramic particles are uniformly dispersed in the solvent, and the mass concentration of the dispersion is both It ranges from 2% to 40%.

[0050] In one example, the second solvent and the fourth solvent The medium is , each Water, N-methylpyrrolidone, ethanol, acetone, etc. At least one of the following is selected: The first nanofiber material and the second nanofiber material are dispersed by high-speed stirring, high-pressure homogenization, sand mill dispersion, etc. Solvent The first nanofiber is uniformly distributed in the and Second nanofiber dispersion liquid The mass concentration at both It ranges from 2% to 30%.

[0051] Where: Multiple The length of the first nanofiber is such that the difference in length is 500 nm or less, i.e. Suitable They may be different as long as they are within the size range. Multiple The length of the second nanofiber is such that the difference in length is 200 nm or less, i.e. Suitable They may be different as long as they are within the size range.

[0052] Here, nanofibers of different lengths are realized based on the selection of nanofiber raw materials, for example, when nanofiber materials of different materials are selected, nanofibers of different lengths may be formed.

[0053] In other examples, nanofibers of different lengths may be formed by corresponding technical solutions.

[0054] The raw nanofiber material or the cut nanofiber material is cut and, by one or more cuts, nanofibers of different lengths are formed.

[0055] Here, by cutting the nanofiber material, a short nanofiber material can be formed based on a raw material of nanofiber material of one length, for example, the nanofiber material can be cut in half of the raw material, or in other examples, it can be achieved without adopting the method of cutting in half.

[0056] Any existing or improved means by which cutting of the nanofiber material can be achieved can be embodied in the embodiments of the present invention, in which case cutting can be achieved by etching the nanofiber material, for example by etching the nanofiber into half its original length.

[0057] Depending on the desired stratification, a single cut or multiple cuts can be made to the feedstock, for example, by first etching the nanofiber material to half the length of the feedstock and then Part Half the length of the nanofiber material is retained, and the other portion of the nanofiber material is cut to half the length to obtain a quarter-length nanofiber material; in other examples, a portion of the quarter-length nanofiber material may be further cut, and the number of cuts can be set as desired.

[0058] Naturally, One Other raw materials for nanofiber materials Nanofiber materials Joining to one end of the raw material, One of the joined nanofiber material; Nanofiber materials Joining to one end of the raw material, One At least one joining step may be performed, joining one end of a joined nanofiber material to one end of another joined nanofiber material, to form nanofiber materials of different lengths through one or more joinings.

[0059] Thus, the objects of joining are: Nanofiber materials One end of the raw material and the other Nanofiber materials It may be a part of the raw material, Nanofiber materials It may be one end of a raw material and one end of a joined nanofiber material, or it may be one end of a joined nanofiber material and one end of another joined nanofiber material.

[0060] Here, by bonding to the nanofiber material, a long nanofiber material can be formed based on a raw material of one length of nanofiber material, for example, two Nanofiber materials By joining the feedstocks together, a double length nanofiber material may be formed, and in other instances, different lengths may be formed. Nanofiber materials This may be achieved using raw (or bonded) nanofiber materials.

[0061] Any existing or modified means capable of achieving bonding of nanofiber materials may be embodied in embodiments of the present invention.

[0062] For example, the conjugation of nanofiber materials may be achieved based on materials with a high content of hydroxyl functional groups (e.g., polyethylene glycol PEG), and the conjugation mentioned above may be achieved by: mixing the nanofiber material to be bonded and a material containing a large amount of hydroxyl functional groups (e.g., PEG) in a solution; adding molecular sieve particles to the solution as a catalyst; and heating and cooling the solution and filtering to remove the molecular sieves to obtain the grafted nanofiber material.

[0063] Take nanocellulose as an example. The ends of nanocellulose have a significantly higher hydroxyl content than the middle region. To increase the length of nanocellulose, the activity of hydroxyls can be fully utilized, and the method is as follows: (1) Nanocellulose is mixed with polyethylene glycol (PEG), and the molecular weight of PEG is 50,000 to 1,000,000 g / mol. PEG Mass ratio of accounts for 1% of the nanocellulose, and the two are thoroughly and uniformly stirred to form the corresponding solution. (2) adding 13A molecular sieve particles to the solution, the particle size being 1 mm to 10 mm, the molecular sieve being a catalyst; (3) 80 over 1-2 hours ℃ to water bathHeat with (4) The mixture is cooled to room temperature and the 13A molecular sieve particles are filtered off to obtain the grafted nanocellulose.

[0064] In the above solution, the nanocellulose can be cross-linked by adding a material (e.g., PEG) containing a large amount of hydroxyl functional groups, and the polymerization reaction between PEG and nanocellulose can be accelerated by using molecular sieves (e.g., 13A molecular sieves) as a catalyst, and finally the structure of nanocellulose-PEG-nanocellulose is formed. Based on the desired hierarchy, one or multiple bonding to the raw material can be realized, for example, the raw material of the nanofiber material is first bonded to twice the raw material, and a part of the nanofiber material with twice the length is reserved, and the other nanofiber material with twice the length is bonded to the raw material or the nanofiber material with twice the length to obtain a nanofiber material with three or four times the length, and in other examples, further bonding can be performed, and the number of bonding times can be set arbitrarily as needed.

[0065] Here, mixing the first ceramic dispersion and the first nanofiber dispersion to obtain the first paste and mixing the second ceramic dispersion and the second nanofiber dispersion to obtain the second paste both include the following: mixing the first ceramic dispersion and the first nanofiber dispersion to obtain the first mixed solution, mixing the second ceramic dispersion and the second nanofiber dispersion to obtain the second mixed solution, and adopting a mixing method such as high-speed stirring, high-pressure homogenization, and sand mill dispersion. Then, adding an adhesive to both the first mixed solution and the second mixed solution, respectively, to obtain the first paste and the second paste. Here, the adhesive is at least one of polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, styrene butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, and polyimide. The adhesive occupies 1% to 10% of the solid mass in the first mixed solution and the second mixed solution, respectively.

[0066] In one example, the film is formed by coating by coating the first paste prepared above on the base film first, drying to obtain the first coating layer, and then coating the first coating layer with the second paste, drying to obtain the coated separator. The coating methods include spray coating, dip coating, microgravure roll coating, print coating, extrusion coating, wire bar coating. At least one of The base film is, for example, a polyolefin base film, the thickness of which is 3 to 30 microns, and the drying temperature is 40 to 130°C. ℃ and the coating speed is 10 to 200 m / min.

[0067] Naturally, drying is the first paste and / or Second paste to first coating layer and / or It is just one method of forming a second coating layer, and the first paste and / or The second paste is then applied to the first coating layer by phase transition. and / or A second coating layer may be formed. and / or How to make the first coating layer from the second paste and / or The present invention does not place any limitations on the manner in which the second coating layer is formed.

[0068] Here, in a preferred embodiment, the method further includes selection of the ceramics and pretreatment of the ceramics prior to dispersion of the ceramics, and specifically, the method is as follows. Specifically, the selection of ceramics includes selecting first ceramic particles and second ceramic particles having different particle sizes, in which the first ceramic particles have an average particle size of 100 to 600 nm, and the second ceramic particles have an average particle size of 10 to 60 nm; The ceramic pretreatment is specifically to add the second ceramic particles to a reaction vessel, add a grafting object to carry out a grafting reaction, and graft fast lithium ion conductive functional groups onto the surfaces of the second ceramic particles. Specifically, the second ceramic particles are added to a solvent and then put into a reaction vessel together, and the grafting object is added, and the fast lithium ion conductive functional groups can be grafted onto the second ceramic particles at a certain reaction temperature, reaction pressure, and reaction time.

[0069] The second ceramic particles are not particularly limited, and are preferably a material having a melting point of 200° C. or more, high electrical insulation, and electrochemically stable within the range of use of a lithium battery. For example, ceramics such as alumina, silica, titanium oxide, zirconia, magnesia, ceria, yttria, and zinc oxide, nitride ceramics such as silicon nitride, titanium nitride, and boron nitride, silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, basic alumina (aluminum hydroxide oxide), potassium titanate, talc, kaolinite, kaolin, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand may be used alone or in combination.

[0070] The first ceramic particles are not particularly limited, and are preferably made of an inorganic material having a melting point of 200° C. or higher, high electrical insulation, and electrochemically stable within the range of use of a lithium battery, and may be the same or different from the second ceramic particles. The solvent may be water, ethanol, acetone, NMP, etc. At least one of The grafting target is polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, methyl isopropyl ketone, etc. At least one ofThe reaction temperature is 100-200°C, the reaction pressure is 0.1-0.5Mpa, and the reaction time is 10-50min. After the reaction is completed, the liquid solvent is removed, leaving a solid, and the second ceramic particles grafted with high-speed lithium ion conductivity can be obtained.

[0071] Based on this, the dispersion of ceramics is specifically The first ceramic particles and the pretreated second ceramic particles are dispersed in a first solvent and a third solvent, respectively, to obtain a first ceramic dispersion and a second ceramic dispersion, respectively.

[0072] Further, embodiments of the present invention further provide a battery comprising the coated separator according to the first aspect of the present invention and its alternative solutions or the coated separator produced using the second aspect of the present invention and its alternative solutions, wherein the battery is, for example, a lithium battery.

[0073] The product performance of several embodiments of the present invention will be analyzed through experiments below. EXAMPLES

[0074] In this embodiment, the coated separator is manufactured by the following steps.

[0075] In selecting ceramics, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the average particle size of the first ceramic particles is 300 nm, the average particle size of the second ceramic particles is 40 nm, and both the first ceramic and the second ceramic are alumina.

[0076] In dispersing the ceramics, the first ceramic particles and the second ceramic particles are uniformly dispersed in N-methylpyrrolidone by high speed stirring to obtain a first ceramic dispersion and a second ceramic dispersion, in which the mass concentration of the first ceramic particles in the first ceramic dispersion and the mass concentration of the second ceramic particles in the second ceramic dispersion are both 20%.

[0077] In dispersing nanomaterials, first and second nanofibers having different lengths are dispersed in N-methylpyrrolidone to obtain a first nanofiber dispersion and a second nanofiber dispersion, where the length L50 of the first nanofiber is 600 nm, the length L50 of the second nanofiber is 300 nm, the dispersion method is high-speed stirring, and the mass concentrations of the first and second nanofibers in the dispersant are both 15%.

[0078] In preparing the paste by mixing, a first ceramic dispersion and a first nanofiber dispersion are mixed to obtain a first mixed solution, a second ceramic dispersion and a second nanofiber dispersion are mixed to obtain a second mixed solution, and a mixing method is adopted of high speed stirring, and then an adhesive is added to the first mixed solution and the second mixed solution, respectively, to obtain a first paste and a second paste. The adhesive is polyvinyl alcohol, and the adhesive accounts for 8% of the solid mass in the first mixed solution and the second mixed solution, respectively, and the mass ratio of the first nanofibers to the first ceramic particles is 1:1, and the mass ratio of the second nanofibers to the second ceramic particles is 1:1.

[0079] In the coating film production, the first paste is coated on one surface of the base film by the coating method, and then dried to form a first coating layer on the surface of the base film, thereby obtaining a semi-finished coated separator, and the second paste is coated on the first coating layer and then dried to obtain a second coating layer on the surface of the first coating layer, thereby obtaining a coated separator. Here, the base film is a polyethylene base film, the thickness of which is 9 microns, and the drying temperature is 100 ℃ and the coating speed is 100 m / min. The thickness of the obtained first coating layer is 0.8 microns and the thickness of the second coating layer is 0.3 microns.

[0080] Here, the first nanofiber and the second nanofiber are specifically one-dimensional nanofibers, which are deposited on the surface of the base film to form a layered structure (i.e., hierarchical nanomaterials of different lengths), and in the process of depositing on the base film, due to surface energy, the longest one-dimensional nanomaterial (which has the largest surface energy, is the most unstable, and is most likely to adhere once it comes into contact with an interface with a small surface energy) is deposited first, the second longest is deposited next, and the shortest nanofiber is deposited last, thus forming a layered structure gradually deposited in order of length. The present invention greatly improves the mixing uniformity and reduces the size difference by mixing nanofibers of similar sizes.

[0081] Using the same method, Examples 2 to 12 and Comparative Examples 1 to 5 were obtained, where the performance of the corresponding separators obtained in Examples 1 to 12 and Comparative Examples 1 to 5 can be seen in Table 1. Except for the differences in the manufacturing parameters shown in Table 1, all the Examples and Comparative Examples are identical to Example 1 in other respects, so the description is omitted here.

[0082] Here, Example 12 shown in Table 1 differs from Example 1 only in that a ceramic pretreatment step was performed on the second ceramic particles before the dispersion of the S2 ceramic. The second ceramic particles were added to a solvent and then put into a reaction vessel together, and the grafting object was added, and a constant reaction temperature, reaction pressure, and reaction time were maintained to graft high-speed lithium ion conductive functional groups onto the second ceramic particles. The solvent was acetone, and the grafting object was polycarbonate. The reaction temperature was 150°C, the reaction pressure was 0.3Mpa, and the reaction time was 20min. After the reaction was completed, the liquid solvent was removed, leaving a solid, and the second ceramic particles with high-speed lithium ion conductivity grafted could be obtained.

[0083] [Table 1-1] [Table 1-2] [Table 1-3] [Table 1-4]

[0084] As can be seen from Table 1 and comparison of Examples 1 to 12, when the first nanofibers and the first ceramic particles are mixed and when the second nanofibers and the second ceramic particles are mixed, the thermal shrinkage at 180°C is less than 5%, the lithium ion conductivity is greater than 1.2mS / cm, and the battery capacity retention rate for 30 days is 98% or more. When the thickness of the first coating layer is thin and the thickness of the second coating layer is increased, the heat resistance is decreased (Examples 1, 2, and 3). This is mainly because the first nanofibers and the first ceramic particles are the main skeleton and directly contact the base film, so the heat resistance of the first coating layer made of the first nanofibers and the first ceramic particles is directly improved, and when the thickness of the first coating layer is thin, the heat resistance is directly decreased. The second coating layer consisting of the second nanofibers and the second ceramic particles is in direct contact with the electrode plate, and its uniformity directly determines the capacity retention rate of the battery; the higher the uniformity, the higher the capacity retention rate of the battery. The thickness of the second coating layer can greatly improve the uniformity of the entire coating layer structure, so that as the thickness of the second coating layer increases, the capacity retention rate of the battery improves (Examples 1, 2, and 3).

[0085] As can be seen from a comparison between Example 1, Example 5, and Comparative Example 3, if the particle diameter of the second ceramic particles in the second coating layer is too large, the capacity retention rate of the battery left at high temperature decreases (Comparative Example 3), and if the particle diameter of the second ceramic particles in the second coating layer is small, the lithium ion conductivity decreases (Example 1, Example 5). As can be seen from a comparison between Example 1 and Example 7, if the length of the second nanofibers in the second coating layer decreases, the lithium ion conductivity decreases. This phenomenon is caused by the fact that, as the length of the second nanofibers increases, the irregularity of the pore size distribution in the second coating layer increases, and the capacity retention rate of the battery decreases, and, as the length of the second nanofibers decreases, the pore size becomes narrower and the lithium ion conduction channel becomes smaller. However, as shown in Example 12, if the particle diameter of the second ceramic particles in the second coating layer decreases, the lithium ion conductivity decreases. particleThe conductivity of lithium ions can be further improved by grafting fast lithium ion conducting functional groups onto the

[0086] As can be seen from the comparison of Example 1, Comparative Example 2, and Comparative Example 4, as the diameter of the first ceramic particles in the first coating layer increases, the heat resistance of the separator decreases, and as the length of the first nanofibers in the first coating layer increases, the heat resistance of the separator also decreases. The main causes of this phenomenon are: Ceramic particle size and nanofiber If the size increases too much, the gaps between the coating layer materials will increase and the contact points with the base membrane will become limited, which will be manifested as the separator being unable to effectively suppress its shrinkage when heat is applied.

[0087] As can be seen from a comparison of Example 1, Comparative Example 1, and Comparative Example 5, when the nanofibers and ceramic particles are irregularly distributed, the capacity retention rate of the battery left at high temperatures is only 95%, which is much lower than the case of layering. When the first nanofibers and the second ceramic particles, and the second nanofibers and the first ceramic particles are mixed, the lithium ion conductivity, the capacity retention rate of the battery left at high temperatures, and the heat resistance are further reduced. The cause of this phenomenon is the nanofibers and ceramic particles. particle When the first coating layer is irregularly distributed, the pore size of the coating layer becomes less uniform and the pore size varies, resulting in a decrease in the capacity retention rate of a battery that is left at high temperatures. Nanofiber materials The second nanofiber Consists of , the second coating layer Nanofiber materials The first nanofiber Consists of In the case of the nanofibers, the size difference between the nanofibers and the ceramics becomes large, so the mixing consistency decreases, while the first coating layer is not easily attached. 1 The introduction of nanofibers into the first coating layer significantly increases the pore size and its inconsistency, which significantly reduces the capacity retention rate of the battery when it is left at high temperatures. 2 The introduction of nanofibers reduces the rigidity of the skeleton, resulting in reduced heat resistance at high temperatures.

[0088] In the description herein, the use of terms such as "one embodiment," "one example," "particular implementation," "one example," and the like means that the specific features, structures, materials, or characteristics described with reference to that example or example are included in at least one example or example of the present invention. In the present specification, exemplary expressions of the above terms do not necessarily refer to the same example or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more examples or examples.

[0089] Finally, the above embodiments are only used to describe the technical solutions of the present invention, and are not intended to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or make equivalent substitutions for part or all of the technical features therein, and such modifications or substitutions do not cause the essence of the corresponding technical solutions to depart from the scope of the technical solutions of the embodiments of the present invention. [Explanation of symbols]

[0090] 10. Base membrane 20, first coating layer 21. The first nanofiber 22. First ceramic particles 30, second coating layer 31. Second nanofiber 32. Second ceramic particles

Claims

1. A coating separator comprising a base membrane and a coating layer structure disposed on at least one surface of the base membrane, The coating layer structure includes at least a first coating layer and a second coating layer, where the first coating layer is disposed on a surface of the base membrane, the second coating layer is disposed on a side of the first coating layer away from the base membrane, the first coating layer includes a first nanofiber material and first ceramic particles, and the second coating layer includes a second nanofiber material and second ceramic particles; the first nanofiber material comprises a number of first nanofibers and the second nanofiber material comprises a number of second nanofibers; A coated separator, characterized in that the difference in length between some of the first nanofibers is 500 nm or less, the difference in length between some of the second nanofibers is 200 nm or less, the length of the first nanofibers is greater than the length of the second nanofibers, and the average particle diameter of the first ceramic particles is greater than the average particle diameter of the second ceramic particles.

2. 2. The coated separator according to claim 1, wherein the first nanofibers have a length of 500 to 1000 nm, and the first ceramic particles have an average particle size of 100 to 600 nm.

3. The coated separator according to claim 2, wherein a mass ratio of the first nanofiber material to the first ceramic particles is 5:1 to 1:

5.

4. 2. The coated separator according to claim 1, wherein the second nanofibers have a length of 100 to 300 nm, and the second ceramic particles have an average particle size of 10 to 60 nm.

5. The coated separator according to claim 4, wherein a mass ratio of the second nanofiber material to the second ceramic particles is 5:1 to 1:

5.

6. 2. The coated separator of claim 1, wherein the first nanofibers have a diameter of 5 to 50 nm, and the second nanofibers have a diameter of 5 to 50 nm.

7. 2. The coated separator of claim 1, wherein a ratio of the thickness of said first coating layer to said second coating layer is greater than 2.

8. The coated separator according to any one of claims 1 to 7, further comprising at least one additional coating layer between the first coating layer and the second coating layer.

9. fast lithium ion conductive functional groups are grafted onto the surfaces of the second ceramic particles; The coated separator according to claims 1 to 7, further characterized in that the high-speed lithium ion conductive functional group includes any one of hydroxyl (-OH), carbonyl (-C=O), fluorine (-F) and carboxyl (-COOH).

10. The coated separator according to any one of claims 1 to 7, characterized in that the first ceramic particles and / or the second ceramic particles are inorganic compounds having a melting point of 200°C or higher, having electrical insulation properties, and being electrochemically stable within the range of use of a lithium battery.

11. The coating separator comprises at least a) ionic conductivity ≧1.2 mS / cm; b) Capacity maintenance rate ≧98%, c) thermal shrinkage at 180 ° C / h ≦ 5%, 2. The coated separator according to claim 1, which satisfies any one of the above conditions.

12. A method for producing the coated separator according to any one of claims 1 to 11, comprising the steps of producing a paste and forming a film by coating, In the preparation of the paste, a first paste including first ceramic particles and a first nanofiber material is prepared, and a second paste including second ceramic particles and a second nanofiber material is prepared; In the film formation by coating, the first paste is coated on at least one surface of the base film to form a first coating layer, and the second paste is coated on the side of the first coating layer away from the base film to form a second coating layer; moreover, preparing the first paste includes dispersing first ceramic particles in a first solvent to obtain a first ceramic dispersion, dispersing a first nanofiber material in a second solvent to obtain a first nanofiber dispersion, and mixing the first ceramic dispersion and the first nanofiber dispersion to obtain the first paste; A method for producing a coated separator, characterized in that the production of the second paste includes dispersing second ceramic particles in a third solvent to obtain a second ceramic dispersion, dispersing a second nanofiber material in a fourth solvent to obtain a second nanofiber dispersion, and mixing the second ceramic dispersion and the second nanofiber dispersion to obtain the second paste.

13. Prior to the preparation of the paste, the method further comprises screening of ceramics, In the selection of ceramics, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the first ceramic particles have an average particle size of 100 to 600 nm and the second ceramic particles have an average particle size of 10 to 60 nm; The method for producing a coated separator according to claim 12, further comprising a pretreatment of the ceramic, the pretreatment of the ceramic comprising carrying out a graft reaction between the second ceramic particles and a graft object, thereby grafting high-speed lithium ion conductive functional groups onto the surfaces of the second ceramic particles.

14. The method for producing a coated separator according to claim 13, wherein the graft object includes any one of polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, and methyl isopropyl ketone.

15. A battery comprising the coated separator according to any one of claims 1 to 11, or a coated separator produced by the method for producing a coated separator according to any one of claims 12 to 14, The battery is further characterized in that the battery is a lithium battery.

Citation Information

Patent Citations

  • Improvements in or relating to storage batteries

    GB580390A

  • Separator, method for producing separator and apparatus for producing separator

    JP2013245428A

  • Separator for lithium ion secondary battery

    JP2020145008A

  • Lithium-ion battery coating solution, lithium-ion battery separator, and lithium-ion battery

    JP2021526299A

  • Separator structure for secondary battery, method for making the separator, and the secondary battery using the same

    US20210359375A1